Osteopontin Stabilizes Metastable States Prior to Nucleation during Apatite Formation - Ibsen, C.; Gebauer, Denis; Birkedal, H. (American Chemical Society, 2016)
© 2016 American Chemical Society.Osteopontin, which is a phosphoprotein with strong ties to in vivo bone mineralization, is shown to change the precipitation pathway of calcium phosphate. We show that the presence of the phosphoprotein, even in minute concentrations, can stabilize an otherwise oversaturated mixture against precipitation. At moderate concentrations, we find that the protein introduces a new intermediate state into the reaction pathway leading to apatite formation. This new intermediate was found to share many characteristics of a coacervate or polymer-induced liquid-like precursor (PILP) phase. Our results show that these types of complex phases should be considered when discussing the mechanisms of bone mineralization on a subcellular level.